PENDIDIKAN TAUHID DALAM KISAH NABI IBRAHIM - Septiyani, Alfrida Dyah (Faculty of Ushuluddin and Humanities, 2019)
The results showed that: 1) Monotheism Education in Surat Al-An'am: 74-83 namely: 1) Monotheism Education Rub?biyah, which is in verse 75 which explains that Allah SWT has shown signs of the greatness of Allah SWT in the sky and grounded to prophet Ibrahim as so that his soul is directed. Then the prophet Ibrahim (as) discovered the truth of the belief in a Godhead through observation and contemplation about the universe by using his fitrah, and this is following verses 76-78. 2) Education of Uluhiyah Tauhid is in verse 74, which explains that the father and the prophets of Abraham made the idols they made into gods. Moreover, verse 79, that is, the sincerity of the prophet Ibrahim as to surrender, confronts his view of Allah SWT. It does not follow his people to associate Allah by way of worshiping other than Him, such as worshiping the stars, the moon, and the idols that they made themselves.3) Implementation of Tauhid Education in Islamic Education: The faith taught by Islam to humans since childhood is critical. Because the goals of Islamic education itself are in harmony with religious goals: 1) To realize a believer who believes and is devoted to Allah SWT.2) Education in Islam seeks to develop and inculcate monotheistic education to humans as optimal as possible to be able to function as a driving force in daily practice. 3) Development and inculcation of monotheism education can be done with learning activities, namely through various institutions. 4) In the school environment, both elementary, middle, and for the development and planting of monotheism, education is carried out through multiple activities, both at the time of KBM and extracurricular. 5) Outside the school, the development and cultivation of human monotheism education start from the family environment